A biblioteca pública no processo de mediação da leitura: o caso da biblioteca pública de Ananindeua “Professora Therezinha Gueiros” - REIS, Vanessa Almeida Ramos dos (2018)
This research is focused on reading and its practice in the public library, whose purpose was to identify the practices to encourage reading through the proper use of the library. We'll talk about reading with an emphasis on the library. To base the theories, the theoretical reference was based on authors with studies related theme; the search was made in books and articles published in area databases. As a practical part, a case study was carried out at the Ananindeua Public Library Professor Therezinha Gueiros, whose argument was the analysis of issues related to the process of stimulating reading and the formation of readers in the unit. When we visited the library it was possible to check how the process of planning, creating actions and events with the aim of encouraging reading. We present some reading projects in place, which are giving a strong incentive to the formation of readers. For this purpose, data were collected through an interview with the librarian and the observation of space. The experience in the library makes us reflect that the taste for reading can be stimulated through developed strategies.